Analysis of the sociodemographic and clinical profile of patients with breast cancer in Petrolina-PE - Ribeiro, Lucimila Teixeira; Britto, Lidiane Régia Pereira Braga de (Seven Editora, 2023)
Objective: To perform the descriptive analysis of the main sociodemographic and clinical characteristics of breast cancer patients followed at the Petrolina Oncology Center - PE between 2010 and 2015. Methodology: A retrospective and descriptive study with a transversal approach, where 670 medical records were analyzed. Results: A predominance of female patients (99.25%) occurred, most of them referred by the Brazilian Unified Health System (SUS) (52.24%), presenting a mean age of 56.15 ± 14.41, race / color (79.25%), non-alcoholics (77.91%), presence of family history of cancer (57.16%) and level of schooling until incomplete primary education (43.58%). Regarding the clinical data, prevalence of the diagnosis in stage I (21.64%) was observed, with the invasive ductal being the most common histological type of tumor (79.40%). The most used therapeutic approach was the surgery associated to the use of chemotherapy, radiotherapy and hormone therapy (30.90%). Radical mastectomy modified with the axillary evacuation procedure, were the most performed surgical intervention (23.58%). At the end of the first treatment, the disease was often stable (74.63%), with a reduced amount of patients performing breast reconstruction (4.95%). Conclusion: A better knowledge of the individuals’ profile affected by breast cancer in the Submédio São Francisco allows health managers and patients to obtain more information about the disease and its epidemiology, as well as clinical and therapeutic characterization of the disease. Such data never before evaluated in the region, may enable the development of more effective strategies in the prevention and diagnosis of breast neoplasia. DOI:https://doi.org/10.56238/alookdevelopv1-081